2019
DOI: 10.3390/en12081535
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Energy Efficiency Improvement of Twenty-Five Countries: A DEA Approach

Abstract: Since energy efficiency and energy improvement are viewed as two of the most important keys of sustainable management, research on energy has become popular and captured much more attention. The current paper aimed to measure the energy efficiency of 25 countries with carbon dioxide (CO2) emissions as well as their energy efficiency improvement. First, a data envelopment analysis (DEA) slack-based model (SBM) was employed to obtain efficiency scores. Second, the Malmquist Productivity Index (MPI) was then used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…The results of this study to a large extent confirm the findings of Liu and Liu [59], who estimated the energy performance of the top 20 CO 2 emitting nations. Wang et al [48] also obtained similar findings, assessing the energy efficiency of 25 nations. These findings are supported by Wang et al [60] and Zhou et al [70] who studied 17 nations and the APEC nations, respectively.…”
Section: Case Scenario 2: Malmquist Productivity Index (Mpi) Without mentioning
confidence: 56%
See 2 more Smart Citations
“…The results of this study to a large extent confirm the findings of Liu and Liu [59], who estimated the energy performance of the top 20 CO 2 emitting nations. Wang et al [48] also obtained similar findings, assessing the energy efficiency of 25 nations. These findings are supported by Wang et al [60] and Zhou et al [70] who studied 17 nations and the APEC nations, respectively.…”
Section: Case Scenario 2: Malmquist Productivity Index (Mpi) Without mentioning
confidence: 56%
“…Elsewhere, there is a growing body of theoretical and empirical literature on energy efficiency that applies the DEA for several countries or regions; these include the US [45]; China [46][47][48][49]; India [50,51]; Japan [52]; and OECD countries [53,54]. In the African context, there exists a lacuna of energy efficiency studies using the data envelopment analysis approach, although there are some important energy efficiency studies in Africa [2,3,[55][56][57][58].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same three air-pollutants were also analyzed by Camarero et al (2013) and they reached similar conclusions, with the exception that the eco-efficiency of NO x emissions did not improve [43]. Regarding energy efficiency improvements, Wang et al (2019) compared the CO 2 emissions in relation to GDP growth from 25 countries and found that India and China are the two worst countries in terms of energy efficiency [54]. A similar study focusing on energy recovery from waste for European Union (EU) member states was produced by Halkos and Petrou (2019) [47].…”
Section: Literature Review-energy-related Country Comparisons With Damentioning
confidence: 81%
“…The environmental performance of investment in terms of renewable energy at the macroeconomic level in European countries was studied in [30]. Wang et al [31] measured the improvement in energy efficiency of twenty five countries using a slack-based DEA approach and Malmquist Productivity Index (MPI). The multiple-criteria decision analysis (MCDA) DEA method was applied in [32] to construct a slacks-based composite indicator for 109 countries worldwide, and the authors of [33] evaluated the effect of clean energy use on total factor efficiencies of 87 countries from 2004 to 2010.…”
Section: Introductionmentioning
confidence: 99%